Geo-Insight MBG: Sebuah Platform Geospasial untuk Mengukur Dampak Program Makan Siang Gratis terhadap Status Gizi Anak - Ashabul Kahpi; Harianto Harianto; Ariastuti Rahman (LKP Unity Academy, 2025)
The Free Nutritional Meal Program (MBG) is a strategic national policy designed to improve the nutritional status of school-aged children. However, impact evaluation remains largely manual and administrative, hindering the identification of priority areas and integrated monitoring of anthropometric changes. This study aims to develop Geo-Insight MBG, a web-based geospatial platform to measure the program’s impact on children’s nutritional status. The methodology employs the Waterfall software development model and quantitative descriptive analysis of height, weight, and body mass index data collected before and after the intervention. System testing demonstrates that the platform successfully visualizes beneficiary distribution, automatically calculates nutritional categories based on z-scores, and generates interactive dashboards and regional heatmaps. Preliminary results from a pilot sample of 15 children indicate that 73.3% showed nutritional improvement, with an average z-score increase of +0.83. While these findings suggest the platform’s potential for enhancing location-based monitoring and data-driven decision-making, the limited sample size necessitates cautious interpretation of the program’s effectiveness. Future studies with larger, multi-regional cohorts are needed to validate these results. Nonetheless, Geo-Insight MBG demonstrates promise as a scalable digital evaluation tool that could support optimized resource allocation and targeted interventions in national school nutrition programs.